1975
DOI: 10.2355/tetsutohagane1955.61.7_1012
|View full text |Cite
|
Sign up to set email alerts
|

Embrittlement Due to the High Temperature Solution Annealing in 18% Ni Maraging Steels

Abstract: Synopsis:Embrittlement due to the high temperature solution annealing (H.T.S.A.) in 18%Ni maraging steels has been reported, but the mechanism is not known. A study has been made of the effects of the solution annealing condition, aging condition and cold working on this embrittlement, and discussions are given on the cause of the embrittlement.The embrittlement is not observed in high temperature solution annealed condition. However, it becomes pronounced with increase in the aging temperature or aging time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Goldberg [6] observed that the PAG contained irregular shaped bands or stringers before recrystallisation, whereas the PAG was full of blocky (massive) martensite after recrystallisation. In the present study, the change of morphology agrees well with previous reports [5,6]. It is evident that the re-dissolution of the intermetallic compounds and recrystallisation, can have an important influence on the martensitic transformation point of C250.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Goldberg [6] observed that the PAG contained irregular shaped bands or stringers before recrystallisation, whereas the PAG was full of blocky (massive) martensite after recrystallisation. In the present study, the change of morphology agrees well with previous reports [5,6]. It is evident that the re-dissolution of the intermetallic compounds and recrystallisation, can have an important influence on the martensitic transformation point of C250.…”
Section: Discussionsupporting
confidence: 93%
“…Hosomi etal. [5] recognized that the stringer martensite was only developed in the range from A f to recrystallisation temperature. Goldberg [6] observed that the PAG contained irregular shaped bands or stringers before recrystallisation, whereas the PAG was full of blocky (massive) martensite after recrystallisation.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] For improvement in these properties, refinement of austenitic grain is useful.3,6,7~ Further intended grain refinement is required to obtain an excellent combination of toughness and ductility at a high strength level, because the higher the strength, becomes the smaller the critical grain size above which tensile specimens fracture within the elastic limit without showing reduction of area.…”
Section: Introductionmentioning
confidence: 99%